Polyamines and microbiota in bicuspid and tricuspid aortic valve aortopathy. (April 2019) - Forte, Amalia; Balistreri, Carmela Rita; De Feo, Marisa; Della Corte, Alessandro; Hellstrand, Per; Persson, Lo; Nilsson, Bengt-Olof
Abstract: Polyamines are small aliphatic cationic molecules synthesized via a highly regulated pathway and involved in general molecular and cellular phenomena. Both mammalian cells and microorganisms synthesize polyamines, and both sources may contribute to the presence of polyamines in the circulation. The dominant location for microorganisms within the body is the gut. Accordingly, the gut microbiota probably synthesizes most of the polyamines in the circulation in addition to those produced by the mammalian host cells. Polyamines are mandatory for cellular growth and proliferation. Established evidence suggests that the polyamine spermidine prolongs lifespan and improves cardiovascular health in animal models and humans through both local mechanisms, involving improved cardiomyocyte function, and systemic mechanisms, including increased NO bioavailability and reduced systemic inflammation. Higher levels of polyamines have been detected in non-dilated aorta of patients affected by bicuspid aortic valve congenital malformation, an aortopathy associated with an increased risk for thoracic ascending aorta aneurysm. In this review, we discuss metabolism of polyamines and their potential effects on vascular smooth muscle and endothelial cell function in vascular pathology of the thoracic ascending aorta associated with bicuspid or tricuspid aortic valve. Highlights: Both mammalian host cells and microorganisms synthesize polyamines. Gut microbiota contribute to polyamines in the circulation. High polyamine levels are found in aorta of patients with bicuspid aortic valve. Polyamines can attenuate vascular inflammation and enhance NO bioavailability.